Protective Effector Cells of the Recombinant Asp f3 Anti-Aspergillosis Vaccine - Diaz-Arevalo, Diana; Ito, James I.; Kalkum, Markus (Frontiers in Microbiology, 2012)
An Aspergillus fumigatus vaccine based on recombinant Asp f3 protein has the potential to prevent aspergillosis in humans, a devastating fungal disease that is the prime obstacle to the success of hematopoietic cell transplantation. This vaccine protects cortisone acetate (CA)-immunosuppressed mice from invasive pulmonary aspergillosis via CD4+ T cell mediators. Aside from these mediators, the nature of downstream fungicidal effectors is not well understood. Neutrophils and macrophages protect immunocompetent individuals from invasive fungal infections, and selective neutrophil depletion rendered mice susceptible to aspergillosis whereas macrophage depletion failed to increase fungal susceptibility. We investigated the effect of neutrophil depletion on rAsp f3 vaccine protection, and explored differences in pathophysiology and susceptibility between CA-immunosuppression and neutrophil depletion. In addition to being protective under CA-immunosuppression, the vaccine also had a protective effect in neutrophil-depleted mice. However, in non-immunized mice, a ten-fold higher conidial dose was required to induce similar susceptibility to infection with neutrophil-depletion than with CA- immunosuppression. The lungs of non-immunized neutrophil-depleted mice became invaded by a patchy dense mycelium with highly branched hyphae, and the peribronchial inflammatory infiltrate consisted mainly of CD3+ T cells and largely lacked macrophages. In contrast, lungs of non-immunized CA-immunosuppressed mice were more evenly scattered with short hyphal elements. With rAsp f3-vaccination, the lungs were largely clear of fungal burden under either immunosuppressive condition. We conclude that neutrophils, although substantial for innate antifungal protection of immunocompetent hosts, are not the relevant effectors for rAsp f3-vaccine derived protection of immunosuppressed hosts. It is therefore more likely that macrophages represent the crucial effectors of the rAsp f3-based vaccine.